Real life drama : the Group Theatre and America, 1931-1940 - Smith, Wendy (Vintage Books, 2013)
Real Life Drama is the classic history of the remarkable group that revitalized American theater in the 1930s by engaging urgent social and moral issues that still resonate today. Born in the turbulent decade of the Depression, the Group Theatre revolutionized American arts. Wendy Smith's dramatic narrative brings the influential troupe and its founders to life once again, capturing their joys and pains, their triumph and defeats. Filled with fresh insights into the towering personalities of Harold Clurman, Lee Strasberg, Cheryl Crawford, Elia Kazan, Clifford Odets, Stella and Luther Adler, Karl Malden, and Lee J. Cobb, among many others. Real Life Drama chronicles a passionate community of idealists as they opened a new frontier in theater.